1993
DOI: 10.1620/tjem.170.219
|View full text |Cite
|
Sign up to set email alerts
|

Three Distinct Southern Blot Hybridization Patterns of HBV-DNA in the Sera of HBV Carriers.

Abstract: The molecular species of hepatitis B virus (HBV)-DNA of 44 sera taken from 25 HBV carriers were examined by Southern blot hybridization with a biotin-labeled HBV-DNA probe and classified into three patterns. Type I consisted of two distinct bands of 4.0 kb and 3.2 kb. Type II consisted of the 4.0 kb and 3.2 kb bands and a smear between these two bands. Type III showed a broad band below 4.0 kb. With endogenous HBV-DNA polymerase reaction, the smear disappeared and 4.0 kb and 3.2 kb bands appeared. After EcoRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The same three hybridization patterns as those reported previously (Yamada et al 1993) were reproducibly identified in this study. Type I consisted of two disinct bands of 4.0 kb and 3.2 kb.…”
Section: Southern Blot Hybridization Patterns Of Serum Hbv Dnasupporting
confidence: 90%
See 4 more Smart Citations
“…The same three hybridization patterns as those reported previously (Yamada et al 1993) were reproducibly identified in this study. Type I consisted of two disinct bands of 4.0 kb and 3.2 kb.…”
Section: Southern Blot Hybridization Patterns Of Serum Hbv Dnasupporting
confidence: 90%
“…HBV DNA spot hybridization Spot hybridization of serum HBV-DNA was performed using a cloned HBV-DNA labeled with biotin as described previously (Yamada et al 1993). …”
Section: Patients and Serological Testsmentioning
confidence: 99%
See 3 more Smart Citations